Toxins and toxicity of Protogonyaulax from the Northeast Pacific - Hall, Sherwood (unpublished, 1982)
A thesis presented to the Faculty of the Univesity of Alaska in partial fulfillment of the requirements for the degree of Doctor of Philosophy.